Response of Nutrient Balance Index in Triticum Aestivum L to Mycorrhizal Inoculation and Phosphorus Fertilizer - Darwesh, Dalshad Azeez; Sahid, Sakar Abdulqadir (Science Journal of University of Zakho, 2013)
A pot experiment was conducted in green house of college of Science, University of Salahaddin Erbil, to study the effect of two levels (0, 20g.pot-1) of mycorrhizal inoculation, four levels (0.0, 25, 50, 75kg.dounm-1) of phosphorus fertilizer and their combination on nutrient balance index in Triticum aestivum L. Experiment was laid out in completely randomized design (CRD) with three replicates. The results indicate that the lowest nutrient balance index (0.833) was recorded from combination treatment (M1P2) compared to control (64.008). The DRIS index ranged from (-14.137 to +14.137) was considered adequate value without mycorrhizal inoculation. Whereas, the DRIS index with mycorrhizal inoculated treatment ranged from (-26.601 to +26.601) was considered adequate value.